Stiffness degradation in granular materials due to chemical dissolution. Issue 2 (9th June 2020) - Viswanath, P.; Das, A.
Abstract : This study proposes a continuum model on stiffness deterioration in reactive granular materials due to chemical weathering. In chemo-mechanical degradation, the packing of the granular material varies as the particle size reduces. A set of chemically treated granular specimens, weathered up to different degrees of dissolution, were prepared. Furthermore, one-dimensional compression (oedometer) tests were carried out, using a soft-ring oedometer, to gain further insight into the variation in stiffness of those specimens. However, no chemical degradation was allowed during the oedometric compression. A thermodynamically consistent stored energy function is proposed to predict the reduction in the stiffness due to grain-size reduction by way of initial chemical treatment. In addition, the state of the material in terms of void ratio and mean stress are considered in the model, keeping in mind the non-linearity of stiffness variation. Finally, the impact of coupled void evolution and grain-size reduction on the elastic stiffness is explored using parametric study.